Bioadhesive supramolecular hydrogel from unprotected, short d, l-peptides with Phe-Phe and Leu-Asp-Val motifs. Issue 20 (12th February 2020) - Cringoli, Maria Cristina; Romano, Chiara; Parisi, Evelina; Waddington, Lynne J.; Melchionna, Michele; Semeraro, Sabrina; De Zorzi, Rita; Grönholm, Mikaela; Marchesan, Silvia
Abstract : Minimalistic and uncapped d, l -peptides self-assemble into bioadhesive hydrogels that successfully mimic the extracellular matrix and lead to high cell viability. Abstract : The uncapped tripeptide D Phe-Phe-Leu acts as self-assembly template to yield supramolecular hydrogel biomaterials. As an example, self-assembling D Phe-Phe-Leu-Asp-Val contains the LDV bioadhesive motif for β1 integrin activation. Hydrogels made of the two peptides successfully mimic fibronectin of the extracellular matrix and lead to high cell viability, adhesion, and spreading.